PTU-043 MNBI is a better marker of oesophageal disease severity compared to using total acid reflux. (June 2019) - Abdul-razakq, Humayra; Raeburn, Amanda; Patel, Kalp; Emmanuel, Anton; Zarate, Natalia; Sweis, Rami
Abstract : Introduction: The Lyon Consensus 2018 describes mean nocturnal baseline impedance (MNBI) as a possible measure of oesophageal mucosa permeability, with lower values associated with damage; however MNBI has not yet entered routine clinical practice. This study aims to determine the relationship of MNBI across three common presentations of reflux; Barrett's oesophagus, NERD and functional heartburn (FH). Methods: Standard pH-Impedance measurements as well as symptom index (SI) were acquired for all patients. The impedance channel at 3 cm was used to calculate MNBI by averaging 3 nocturnal 10 minute intervals 1 hr apart. Consecutive tracings between 2014 and 2016 for 3 reflux subgroups were analysed; 22 Barrett's Oesophagus (13 on proton pump inhibitors; PPI), 26 NERD and 26 FH. Results are presented as median (IQR; interquartile ratio). Comparisons were made using Kruskall-Wallace test and Mann-Whitney U test as appropriate. Correlations were performed using Spearman's correlation coefficient. Results: There was no significant difference in total reflux (TR) between patients with Barrett's (median TR 11.2% (2.5%, 18.7%) and NERD (8.1% (5.5%, 12.9%) (p=0.497). The difference with FH (TR 22% (12%, 34%) is defined by the entry criteria (p<0.0001). SI was significantly lower in Barrett's (SI 4% (0%, 25.6%) than NERD (30% (0%, 45.2%) (p=0.48), but not FH (0% (0%, 7.9%) (p=0.129). There was no statistically significant difference in MNBI between Barrett's while on or off PPIs (p=0.556). There was also no difference in MNBI between 9 patients with persistent Barrett's who had attempts at ablation therapy compared to the 13 who had not (p=0.96). Using the Kruskall-Wallace test, there was a significant difference observed in MNBI between all 3 categories of reflux (p<0.0001). Specifically, there was a difference in patients with Barrett's (median MNBI 429.5Ω(293Ω, 950Ω) compared to NERD (1160Ω(964.5Ω, 2764Ω) (p=0.003) and FH (3355Ω(2866.5Ω, 3809.25Ω) (p<0.0001). There was also a significant difference in patients with NERD compared to FH (p<0.0001). There was a moderately inverse correlation between Barrett's segment length (median 6 cm (3 cm, 10 cm) and MNBI (r= −0.436; p=0.038). Conclusion: In keeping with the published literature, this study shows that severity of reflux disease, as measured by ambulatory pH-impedance monitoring, was not dissimilar between Barrett's oesophagus and NERD, while symptom burden was greater in NERD. On the other hand, MNBI can differentiate between the disease states despite the reduced symptom burden. Also, it correlates with the degree of mucosal damage associated with Barrett's regardless of PPI use or previous therapy. MNBI may be a better marker of reflux disease severity than standard pH measurements.